Calcified Cavitating Mesenteric Lymph Node Syndrome: Case Presentation and Literature Review - Dipinder S Keer; Paul Jeon; Mark R Borgaonkar; Stefan Potoczny (Canadian Journal of Gastroenterology)
Cavitating mesenteric lymph node syndrome (CMLNS) is a rare complication of celiac disease. Globally, only 36 cases of CMLNS have been reported to date. The present article reports an incidence of its unique pathology and possible complications of celiac disease, followed by a review of the syndrome. A case involving a 51-year-old man with celiac disease who was referred to hospital because of a non-tender abdominal mass is described. Plain film x-ray of the abdomen revealed fine curvilinear calcifications in the left lower quadrant. A complex, cystic-appearing, lobulated mass with somewhat echogenic walls most consistent with calcifications was revealed on subsequent ultrasound (US) imaging. Colour Doppler imaging showed no evidence of vascularity within the lesion. Computed tomography (CT) imaging showed a thin rim of calcification in the walls of multiple cystic components. Enhanced magnetic resonance (MR) imaging revealed a mixed solid and cystic multiloculated mass, with fat-fluid layers originating from the root of the small bowel mesentery. A CT-guided biopsy was performed. The fine-needle aspirate revealed calcified matter with no associated cellular material. No malignant cells were seen; CMLNS was established as the diagnosis. To the authors’ knowledge, there are no previous reports in the literature describing the finding of rim calcification on US or MR imaging in the setting of CMLNS. CMLNS is an important diagnosis to consider, particularly in patients with a history of celiac disease. The finding of rim calcification on US in the setting of cavitating mesenteric adenopathy should prompt further diagnostic imaging studies such as CT or MR imaging. These may lead to additional pathology studies such as a CT-guided biopsy to further characterize the lesion at the cellular level, to investigate potential malignancy and to further guide follow-up and patient management.